Deixis Analysis in Mark Zuckerberg’s Testimony in the United States Congress - Nurjannah Nurjannah; Sahur Saerudin (STKIP Taman Siswa Bima, 2025)
This study analyzes the use of deixis in Mark Zuckerberg’s testimony in the United States Congress, focusing on how deictic expressions contribute to meaning, positioning, and speaker-hearer relations in political discourse. Deixis, a central concept in pragmatics, refers to words and phrases such as pronouns, temporal expressions, and spatial indicators that require contextual information for interpretation. This research employed a qualitative descriptive method with a pragmatic approach. The primary data for this research consists of video recordings of Mark Zuckerberg’s congressional hearings in Youtube channel. The utterances of Mark Zuckerberg and Senators became the object of the research to be investigated. The findings show that the deictic markers employed during testimony in Congress categorized into three types; they are personal, temporal, and spatial deixis. Zuckerberg and Senators skillfully employs deixis to construct an image of accountability, collaboration, and respect, while subtly shifting responsibility through strategic pronoun use. By examining how deixis functions in Zuckerberg’s testimony, the research contributes to broader insights in political linguistics, discourse analysis, and pragmatics.